1992
DOI: 10.1007/bf00231834
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of transgenic plants of Prunus armeniaca containing the coat protein gene of Plum Pox Virus

Abstract: A system was developed which allows the transfer of foreign genes into apricot cultivars. We report the transformation and regeneration of Prunus armeniaca plants with Agrobacterium tumefaciens strain LBA 4404 containing various binary plasmids, pBinGUSint, carrying the marker gene ß-glucuronidase (GUS) and pBinPPVm, carrying the coat protein gene of Plum Pox Virus (PPV). The marker gene GUS was used for optical evaluation of the efficiency of the transformation system. The coat protein gene of PPV was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(23 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The final MBC results are indicated in Table 4. It can be seen that the MBC's for both carbenicillin and Examples only 250 mg 1-1 of carbenicillin (da Camara Machado, 1992;Sarria et al, 1994) and 200-300 mg 1 -l of cefotaxime (Maheswaran et al, 1992;Jacq et al, 1993;Pugliesi et al, 1993;De Bondt et al, 1994) are employed are commonly present in the literature. Studies carried out by Martin et al, (1990) and Valles and Lasa (1994) indicated that Agrobacteriurn was still visible on plates with these concentrations of antibiotics.…”
Section: Minimum Bactericidal Concentrationmentioning
confidence: 97%
See 1 more Smart Citation
“…The final MBC results are indicated in Table 4. It can be seen that the MBC's for both carbenicillin and Examples only 250 mg 1-1 of carbenicillin (da Camara Machado, 1992;Sarria et al, 1994) and 200-300 mg 1 -l of cefotaxime (Maheswaran et al, 1992;Jacq et al, 1993;Pugliesi et al, 1993;De Bondt et al, 1994) are employed are commonly present in the literature. Studies carried out by Martin et al, (1990) and Valles and Lasa (1994) indicated that Agrobacteriurn was still visible on plates with these concentrations of antibiotics.…”
Section: Minimum Bactericidal Concentrationmentioning
confidence: 97%
“…Various antibiotics have been employed to eliminate Agrobacterium following transformation, but very few authors actually test to ensure that the antibiotics succeed. Several examples of the use of carbenicillin at 500 mg 1-1 (Radke et al, 1988;Moloney et al, 1989;da Camara Machado et al, 1992;Eapen and George, 1994) and more recently cefotaxime at 200-500 mg 1-1 Hassan et al, 1993;Jacq et al, 1993;Calfalonieri, 1994;Howe et al, 1994;van der Hoeven et al, 1994) exist, but not one tested to ensure that bacterial elimination occurred.…”
Section: Introductionmentioning
confidence: 98%
“…However, there are limitations to achieving this, due to the lack of superior plant material. Improvement of perennial crops through traditional breeding methods is a long-term effort because of their long generation time, their high level of heterozygosity and the fact that many backcrosses are necessary to eliminate undesirable traits (Laimer da Câmara Machado et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In the same period, other works reported poor bud generation from P. persica explants such as immature endosperms (Meng and Zou, 1981), zygotic embryo-derived calli (Hammerschlag et al, 1985;Bhansali et al, 1990;Scorza et al, 1990a), immature and mature (Pooler and Scorza, 1995) cotyledons. Most of the studies describing genetic transformation in peach have described the use of A. tumefaciens infection in either immature or mature explants (Hammerschlag et al, 1989;Scorza and Sherman, 1996;Pérez-Clemente et al, 2004;Padilla et al, 2006); in general, targeting on immature tissues leads over the use of mature explants in woody species (da Câmara Machado et al, 1992;Ye et al, 1994). In those experiments, the use of cytokinines (BAP, kinetin, zeatin or isopentyladenine) has been reported in order to induce regeneration of immature cotyledons, although the number of produced buds has been extremely low.…”
Section: Towards Peach Genetic Transformationmentioning
confidence: 99%